Vagueness-Adaptive Logic: A Pragmatical Approach to Sorites Paradoxes - Van Kerkhove, Bart; Vanackere, Guido (Studia Logica, 2003)
This paper defends a pragmatical approach to vagueness. The vagueness-adaptive logic VAL is a good reconstruction of and an excellent, instrument for human reasoning processes in which vague predicates are involved. Apart from its proof-theory and semantics, a Sorites-treating model based on it is presented, disarming the paradox. The paper opens perspectives with respect to the construction of theories by means of vague predicates.
Keywords: adaptive logic; construction of scientific theories; paraconsistent logic; philosophical logic; philosophy of language; Sorites paradox; vagueness